2022
DOI: 10.3390/molecules27123940
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and In Vitro Release of Curcumin-Loaded IRMOF-10 Nanoparticles and Investigation of Their Pro-Apoptotic Effects on Human Hepatoma HepG2 Cells

Abstract: Curcumin (CUR) has a bright future in the treatment of cancer as a natural active ingredient with great potential. However, curcumin has a low solubility, which limits its clinical application. In this study, IRMOF-10 was created by the direct addition of triethylamine, CUR was loaded into IRMOF-10 using the solvent adsorption method, and the two were characterized using a scanning electron microscope (SEM), X-ray diffraction (XRD), dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FTIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Comparison of the diffractogram of the synthesized MOF with literature data demonstrates the conformity of the materials and the correctness of the synthesis [65,67,100,202]. Identification of functional groups and bonds in the structure is possible by Fourier transform infrared spectroscopy (FTIR) [102,152,162,167,187,209,212] and μRaman spectroscopy [146,152,212]. A comparison of the bands present on the spectrum of pristine MOF with the spectral bands of the drug@MOF composite is necessary to determine the loading efficiency of the drug.…”
Section: Post Synthetic Strategymentioning
confidence: 89%
See 1 more Smart Citation
“…Comparison of the diffractogram of the synthesized MOF with literature data demonstrates the conformity of the materials and the correctness of the synthesis [65,67,100,202]. Identification of functional groups and bonds in the structure is possible by Fourier transform infrared spectroscopy (FTIR) [102,152,162,167,187,209,212] and μRaman spectroscopy [146,152,212]. A comparison of the bands present on the spectrum of pristine MOF with the spectral bands of the drug@MOF composite is necessary to determine the loading efficiency of the drug.…”
Section: Post Synthetic Strategymentioning
confidence: 89%
“…Then, the use of a water-sensitive metalorganic framework can enable drug delivery, as well as accelerate the achievement of a minimum therapeutic dose. An example of such a drug is curcumin (CUR) [209,210].…”
Section: Post Synthetic Strategymentioning
confidence: 99%
“…Through curcumin-labeling and uptake assays we corroborated that BisBAL NP were effectively internalized into tumor cells, as previous studies suggested. 35,36 Yin et al 37 described the internalization of curcumin-loaded IRMOF-10 nanoparticles after a 30-min exposure. BisBAL NP internalization into A549 cells also occurred within 30 min and augmented with time, which correlated with timelines of more severe growth inhibition.…”
Section: Discussionmentioning
confidence: 99%